2014
DOI: 10.1073/pnas.1316390111
|View full text |Cite
|
Sign up to set email alerts
|

ATP turnover by individual myosin molecules hints at two conformers of the myosin active site

Abstract: Coupling of ATP hydrolysis to structural changes in the motor domain is fundamental to the driving of motile functions by myosins. Current understanding of this chemomechanical coupling is primarily based on ensemble average measurements in solution and muscle fibers. Although important, the averaging could potentially mask essential details of the chemomechanical coupling, particularly for mixed populations of molecules. Here, we demonstrate the potential of studying individual myosin molecules, one by one, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 37 publications
5
38
0
Order By: Relevance
“…This suggested that the high duty ratio of Nt 175kDa myosin-11 may result from a rate-limiting ADP release step of the actin bound state of the myosin. Our results from the in vitro motility experiments with low and high [Mg 2+ ] free concentrations indicate the existence of Mg 2+ -sensitive states that influence ADP release to a similar extent as reported for processive myosin-5 motors (31,67,68).…”
Section: Discussionsupporting
confidence: 77%
“…This suggested that the high duty ratio of Nt 175kDa myosin-11 may result from a rate-limiting ADP release step of the actin bound state of the myosin. Our results from the in vitro motility experiments with low and high [Mg 2+ ] free concentrations indicate the existence of Mg 2+ -sensitive states that influence ADP release to a similar extent as reported for processive myosin-5 motors (31,67,68).…”
Section: Discussionsupporting
confidence: 77%
“…Similar kinds of time periods have been observed recently by Amrute‐Nayak et al. for individual myosin molecules due to ATP turnover at the active site . They found two types of dwell times for the myosin molecules‐one shorter time of ∌0.5 sec and a longer time ∌3‐4 sec.…”
Section: Discussionsupporting
confidence: 84%
“…A correction of background noise was performed by calculating the average intensity of the perimeter around the ROI 53 . We measured the on-time by fitting the data to a double exponential decay and defined the slower rate as the ATP binding rate, thus giving a complete ATPase cycle 43 . The ATP binding rate of Cy3-EDA-ATP was corrected to the rate of normal ATP by a factor of 2.8 42 .…”
Section: Objective-type Evanescent Field Darkfield Microscopy and Datmentioning
confidence: 99%